Barium nanoparticles enhance efficacy of external beam radiation therapy in a preclinical basal-like mammary cancer mouse model - Albers, Jonas; Markus, Andrea; Svetlove, Angelika; Kraupner, Alexander; Briel, Andreas; Alves, Frauke; Dullin, Christian (Scientific reports, 2025)
External beam radiation therapy (RT) using high energy x-rays is a commonly applied cancer treatment. A major advantage of RT is its unspecific nature which allows using RT in many cancer entities. RT however causes the well-known side effects on healthy tissue in the irradiated areas. Therefore, enhancing the efficacy of RT at the tumor site while simultaneously lowering the overall radiation dose has been a long term goal. Heavy metal-based contrast agents such as gold, hafnium, gadolinium and iodine have already been proposed as radio-enhancers and are partially in clinical trials. Here we present barium sulphate (BaSO4) nanoparticles as novel radio-enhancer for RT validated in a syngenic mouse breast cancer model. We demonstrate that these particles in combination with low energy RT significantly reduced tumor growth when compared to untreated controls and tumors that received RT only. Despite the fact that the absorption probability decreases with increasing photon energy, we see a stronger anti-tumoral effect at energies around 90 keV which would allow a translation of this approach into a clinical RT setting. Due to the strong contrast of barium in computed tomography such (BaSO4) nanoparticles could be used for both, better tumor delineation as well as for enhancing RT response.
Veröffentlicht: 30. Mai 2025
Gesehen am 17.09.2025